PENGUKURAN PRODUKTIVITAS DENGAN METODE APC PADA INDUSTRI MINUMAN JENIPER CV MUSTIKA FLAMBOYANT KUNINGAN â JAWA BARAT - , ROBIYATUL ADAWIYAH, Ir. Pujo Saroyo, M.Eng.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2014)
CV. MUSTIKA FLAMBOYANT is one of beverage industry which produces Syrup Jeniper and Fresh Drink Jeniper. The production process is use lime squeeze, as raw material. The purpose of this productivity measrument was to evaluate the productivity measrument by using American Productivity Center (APC) methode, during 2012-2013. This methode have 5 criteria, as total productivity, partial productivity of material, partial productivity of labour, partial productivity of capital, and partial productivity of energy The result showed that the productivity was fluctuative. Index of total productivity was 96,80%